An AM1 semiempirical study of the mechanism of sintering for ZnO in the presence of water and carbon dioxide - Vila, Fernando; Ventura, Oscar N.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier, 1994)
AM1 calculations were performed for the absorption of H2O and CO2 molecules on the surface of model ZnO crystals. The absorption of isolated molecules of each species and the co-absorption of both compounds simultaneously were considered. It was found that the absorption of H2O near a site where CO; is already absorbed favors the process of sintering, in agreement with the experimental findings. This is explained by the formation of Zn(OH)CO3H bound to the surface, a more mobile species than the ZnO unit itself. The roundening of the grains observed in atmospheres containing dry CO2 but suppressed when H2O is present, is also explained by these calculations. After absorption of CO2, the rupture of one bond - so that diffusion of the ZnCO3 species on the surface is allowed - requires much less energy than the breaking of two bonds, necessary for ZnO migration. These facts explain why the speed of surface transport does not decrease in CO2 atmospheres while sintering is indeed slowed down. © 1994.